ANALYSIS OF INVENTORY RECORDING AND VALUATION METHODS AT ELPETIGAI TASIKMALAYA CONSUMER COOPERATIVE BASED ON PSAK 14 - Ai Siti Rohimah; Nijar Kurnia Romdoni; Rani Ligar Fitriani (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the inventory recording and valuation methods applied by the Elpetigai Tasikmalaya Consumer Cooperative based on the provisions of PSAK 14. The research method employed is descriptive qualitative, supported by quantitative analysis, through documentation studies, interviews, and financial statement analysis for the period of 2022 to 2024. The results of this study indicate that the cooperative uses a perpetual inventory recording system and the FIFO (First In, First Out) valuation method, which largely complies with PSAK 14. However, in terms of disclosure, the cooperative has not fully met the standards, as it does not include detailed accounting policies and inventory impairment information. This non-compliance affects the transparency and reliability of the financial statements, which may influence managerial decision-making. The study highlights the importance of implementing updated accounting standards to enhance the credibility of financial reporting and provides recommendations for improving inventory management to strengthen the cooperative’s financial stability and operational efficiency.